GOBLET: an open-source geographic overlaying database and query module for spatial targeting in agricultural systems - Quirós, Carlos F.; Thornton, Philip K.; Herrero, Mario; Notenbaert, An Maria Omer; González Estrada, E. (Elsevier, 2009)
We describe the development of an open-source mapping and query utility. The impetus for its development came originally from the need to be able to locate, spatially, target populations of resource-poor livestock keepers in the developing world, and to identify livestock management interventions that may be appropriate for these households. The tool was developed using open-source software, to facilitate its transfer and use. It brings together a considerable amount of spatial data from many sources, and allows users to overlay these geographic areas to identify a “domain” where characteristics like human population, area, and the number of livestock may vary. The tool serves as the core of several applications, including an ex ante impact assessment framework to help answer questions relating to improved targeting of fodder interventions in Kenya, and a communication tool for poverty related information in Africa.